THE PROFITABILITY INDICATORS OF COMMERCIAL BANKS IN THE REPUBLIC OF UZBEKISTAN AND THEIR MODERN STATE - Chartayev Asqar; Xolmamatov Farhod (Scholar Express Journals, 2022)
The current article is devoted to the profitability of the commercial banks of the Republic of Uzbekistan. Hence, the main purpose of the given article is to investigate and analyze the current state, development directions and prospects of the profitability indicators in commercial banks. In addition, the article presents several imperative recommendations, facilitating to raise the efficiency of commercial banks in Uzbekistan.
Keywords: return; recommendations; imperative; efficiency